THE PRACTICAL VALUE OF POLITICAL SCIENCE: BEYOND THE CLASSROOM - Aadil Ahmad Shairgojri (RADJA PUBLIKA, 2023)
The study is an attempt to explore the practical significance of studying political science beyond the confines of the classroom. It outlines to illuminate the real-world applications of political science principles and knowledge in various contexts, from career choices to everyday decision-making. It aims to highlight the diverse career opportunities available to individuals with a background in political science, ranging from public policy to law and government roles. It also aims to underscore the importance of political science education in fostering informed and engaged citizens who actively participate in democratic processes. It aims to provide concrete examples and case studies demonstrating how political science concepts and skills contribute to addressing global issues, resolving conflicts, and shaping public policies. The study seeks to advocate for lifelong learning, emphasizing that political science equips individuals with critical thinking, research, and analytical skills that continue to benefit them throughout their lives. By addressing these objectives, this article underscores the enduring relevance of political science in shaping both personal and societal success.